Oxygen-enriched gasification of lignocellulosic biomass: Syngas analysis, physicochemical characteristics of the carbon-rich material and its utilization as an anode in lithium ion battery. (1st December 2020) - Chen, Tianju; Zhang, Juan; Wang, Zhiqi; Zhao, Ruidong; He, Jianjiang; Wu, Jinhu; Qin, Jianguang
Abstract: Syngas from conventional biomass gasification has low calorific value, low H2 /CO ratio, and high tar content. Oxygen and steam gasification are effective ways to improve the quality of syngas. Gas-carbon co-generation is possible due to the lower temperature at the bottom of the downdraft fixed-bed gasifier. Oxygen-enriched gasification of biomass is investigated in this work. The H2 content in the syngas increased from 34 v% to 45 v% when steam was added. The physicochemical characteristics of the activation carbon (AC) are determined by the Brunauer-Emmett-Teller (BET), Raman, Fourier transform infrared spectrometry (FTIR), X-ray diffractometer (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and transmission electron microscope (TEM). In addition, the AC from the activation of carbon-rich production used as anode in lithium ion batteries (LIBs) is attempted. The BET of the ACo and ACo-s is 1715.32 m 2 g −1 and 1409.02 m 2 g −1, respectively. The biomass-derived carbon material had less graphitic crystalline structure, less functional groups and graphene-like porous structure after activation. At the current density of 100 mA g −1, a reversible lithium storage capacity of 327 mAh g −1 for a carbon-based electrode is obtained. This research provides a new roadmap for high-value-added products from the thermo-chemical conversion of biomass. Highlights: Oxygen-enriched gasification of biomass is investigated. Oxygen and steam are investigated as gasification agents. The characteristics of graphene-like porous active carbon are investigated. Biomass-derived char is used as electrode in lithium ion batteries is evaluated.